Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2022
DOI: 10.18653/v1/2022.acl-long.222
|View full text |Cite
|
Sign up to set email alerts
|

Misinfo Reaction Frames: Reasoning about Readers’ Reactions to News Headlines

Abstract: Even to a simple and short news headline, readers react in a multitude of ways: cognitively (e.g. inferring the writer's intent), emotionally (e.g. feeling distrust), and behaviorally (e.g. sharing the news with their friends). Such reactions are instantaneous and yet complex, as they rely on factors that go beyond interpreting factual content of news. Headline Reader"they are lying to us." Writer IntentReader Perception "feel distrust" Reader Action"not trust the government"Likelihood of Spread "likely to sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Most similar to our work is the work by Gabriel et al [27] that creates "perceived" news frames from headlines regarding how people think about misinformation. They argued that an effective way to predict how news headlines will influence readers requires understanding how readers perceive the intent behind the news.…”
Section: Semantic Analysis and Understanding The Newsmentioning
confidence: 58%
See 1 more Smart Citation
“…Most similar to our work is the work by Gabriel et al [27] that creates "perceived" news frames from headlines regarding how people think about misinformation. They argued that an effective way to predict how news headlines will influence readers requires understanding how readers perceive the intent behind the news.…”
Section: Semantic Analysis and Understanding The Newsmentioning
confidence: 58%
“…In this work, we also explore implicit items within the text, e.g., estimating implicit sentiment towards the cyclist mentioned in the headline from the writer's perspective. Our framework builds upon the work of [24,27,67] by integrating their key insights into a hierarchical framework for analyzing the pragmatic meaning of news headlines. Our framework will allow us to assess the ways in which news organizations structure their coverage of events or subjects and to evaluate the impact of this coverage on public attitudes and perceptions.…”
Section: Semantic Analysis and Understanding The Newsmentioning
confidence: 99%
“…Tan et al [14] analysed the effect of the content of a tweet on its reach. More recent studies like Gabriel et al [8] demonstrated how the reach of news articles can be estimated using models based on GPT-2 [10] and T5 [11]. However, their approaches provide only a coarsegrained analysis and do not significantly contribute to performing a comparative analysis.…”
Section: Related Workmentioning
confidence: 99%
“…The first heuristic baseline fine-tunes FLANG-RoBERTa [12] to make direct predictions. To evaluate the feasibility of deploying zero-shot LLMs for the proposed task, we let FLAN-UL2 [15,18], Claude, and React T5 [8] make predictions. Going one step further, we solicit various LLMs' analysis of 𝑡1 and 𝑡2 to determine which LLM can guide the classification model to deliver enhanced performance.…”
Section: Experiments 51 Experimental Settingsmentioning
confidence: 99%
“…Pennycook et al (2020) show that people tend to believe false claims about COVID-19 and share false information when they do not think critically about the accuracy and veracity of the information. Recent work aims at understanding reader perception of news reliability (Gabriel et al 2022). Kouzy et al (2020) show that ∼ 25% of COVID-19 messages contain some form of misinformation and ∼ 17% contain some unverifiable information.…”
Section: Related Workmentioning
confidence: 99%